1987
DOI: 10.1136/hrt.58.4.385
|View full text |Cite
|
Sign up to set email alerts
|

Gallium-67 myocardial imaging for the detection of myocarditis in the acute phase of Kawasaki disease (mucocutaneous lymph node syndrome): the usefulness of single photon emission computed tomography.

Abstract: Myocardial imaging with gallium-67 citrate was used to detect myocarditis in 46 consecutive infants and children (31 boys and 15 girls, mean age 21 months) with Kawasaki disease. In all of them planar imaging (group A) was performed at 6 hours and at 48 or 72 hours after the intravenous administration of a mean (SD) dose of gallium-67 citrate (0.07 (0.02) mCi/kg). Thirty four patients (24 boys and 10 girls, mean age 21 months) also had single photon emission computed tomography imaging (group B) soon after pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 9 publications
1
28
0
Order By: Relevance
“…[4][5][6][7] In the past, myocardial inflammation has been documented in up to 50% to 70% of patients early in the KD course with the use of different diagnostic methods. [8][9][10] This finding has been supported by autopsy and biopsy studies showing that almost all patients had some signs of myocarditis, pericarditis, or valvulitis. 11,12 Persistent myocardial abnormalities up to >10 years after disease onset have been observed in specimens of the right ventricular (RV) myocardium.…”
supporting
confidence: 62%
“…[4][5][6][7] In the past, myocardial inflammation has been documented in up to 50% to 70% of patients early in the KD course with the use of different diagnostic methods. [8][9][10] This finding has been supported by autopsy and biopsy studies showing that almost all patients had some signs of myocarditis, pericarditis, or valvulitis. 11,12 Persistent myocardial abnormalities up to >10 years after disease onset have been observed in specimens of the right ventricular (RV) myocardium.…”
supporting
confidence: 62%
“…34,128 Myocardial inflammation has been documented in 50% to 70% of patients using 67Ga citrate scans (planar or singlephoton emission CT) 129 and 99mTc-labeled white blood cell scans. [130][131][132] The severity of myocarditis does not appear to be associated with the risk of coronary artery aneurysms, however.…”
Section: Myocarditismentioning
confidence: 99%
“…KD is now the leading source of acquired heart disease in children [17,28]. Prior studies have clearly identified the presence of myocardial involvement in the acute phase of KD, specifically myocarditis that has been shown to be associated with subclinical and clinical left ventricular dysfunction [2,9,11,12,14,16,18,27]. Standard therapy for patients with acute KD is treatment with intravenous immune globulin (IVIG) which reduces the risk of CAL from 25 to 5 % [19].…”
Section: Introductionmentioning
confidence: 98%